Implementation of Integrated Marketing Communication for ERIGO Brand Through Instagram - Rosita, Lisa; Hariyati, Farida; Akbari, Deni Adha; Agustini, Vilya Dwi (Technium Social Sciences Journal, 2023)
Today, the internet has made many things easier for business, including ERIGO, a local fashion brand from Indonesia. With the rapid development of fashion trends, consumers desire to be looked modern, stylish, and fashionable. This brand adopts a neutral fashion, making it suitable for individuals of any gender. In its marketing strategy, ERIGO incorporates Integrated Marketing Communication (IMC). This research examines the application of IMC to ERIGO brand through the Instagram social media platform. The study used a qualitative descriptive approach with a content analysis methodology, incorporating a literature study and documentation data collection method. The study's results indicate that the utilization of hashtags and visually appealing content has a positive impact on brand awareness, contributing to the formation of a positive image for ERIGO. Furthermore, ERIGO has effectively established relationships with its target audience, collaborated closely with influencers to expand its reach, and presented interesting, high-quality visual content. The target audience for ERIGO brand can be defined based on gender, specifically as unisex. This research contributes significantly by offering valuable insights into implementing Integrated Marketing Communication (IMC) for ERIGO brand through the Instagram social media platform.